Optimalisasi Pembuatan Laporan Harian Maintenance Dan Test Running Wheel Tractor Dengan Menggunakan Quick Response Code Yang Terhubung Pada Google Form - Arnas, Yenni; Novi Mediaswati, Cristina; Angga Subekti, Ibnu; Ardianti, Novia; Isnaini, Mohamad; Aufar Zhafari, Muhammad (Program Studi Teknik Mekanikal Bandar Udara, 2024)
Maintenance and Test Running are important activities in maintaining the performance and reliability of the wheel tractor. To facilitate the daily reporting process for Maintenance and Test Running, an efficient and practical system is needed. Therefore, in this study, optimization of making daily reports was carried out using the Quick Response (QR) code connected to Google Form. This research is expected to increase efficiency in preparing Maintenance and Test Running daily reports on wheel tractors. The QR code system connected to Google Form can be used as a practical solution to reduce the time and effort required in the reporting process. Thus, maintenance and testing of wheel tractors can be carried out more efficiently and accurately, thereby increasing the performance and reliability of the equipment.